Accurate species discrimination of Fasciola hepatica from Türkiye based on the fatty acid binding protein type I (FABP type I) gene and phylogenetic analysis using mitochondrial DNA - Celik, Figen; Tashiro, Michiyo; Simsek, Sami; Balkaya, Ibrahim; Sato, Yukita; Ichikawa-Seki, Madoka (Elsevier, 2025)
Accurate species discrimination based on a robust nuclear protein-coding gene marker is essential for Fasciola spp. because of the presence of F. hepatica, F. gigantica, and hybrid Fasciola flukes that originate from the interspecific hybridization between the two species in Asia. Molecular identification of Fasciola species uses multiplex polymerase chain reaction (PCR) targeting phosphoenolpyruvate carboxykinase (pepck) and PCRrestriction fragment length polymorphism (RFLP) targeting DNA polymerase delta (pold). However, these methods have demonstrated limitations, including misidentification errors. In this study, we aimed to investigate the reliability of multiplex PCR using the fatty acid binding protein type I (FABP type I) gene as a species identification marker. In this study, 75 liver flukes were determined as F. hepatica using FABP type I. FABP type I was more accurate and useful for species identification of F. hepatica than previously reported markers, pepck and pold, as no discrimination errors were observed, whereas misdiagnosis and amplification failure occurred in pepck and pold for five and 13 flukes, respectively. We also aimed to analyze the phylogeny of Turkish Fasciola flukes based on nucleotide sequences of the NADH dehydrogenase subunit 1 (nad1) gene of mitochondrial DNA. Notably, the Turkish F. hepatica population showed greater genetic diversity than the reference populations from the previous studies, suggesting that the Turkish population is much older. This supports the idea that F. hepatica originated in the Fertile Crescent, the area adjacent to T & uuml;rkiye, as proposed previously.
Keywords: Fasciola hepatica; T & uuml;rkiye; Pepck; Pold; FABP typeI; nad1